Association between Duration of Exercise (MET Hours per Week) and the Risk of Decreased eGFR: A Cross-Sectional Study Based on a Large Chinese Population - Jie Wang; Yijun Li; Kang Chen; Wenhua Yan; Anping Wang; Weiqing Wang; Zhengnan Gao; Xulei Tang; Li Yan; Qin Wan; Zuojie Luo; Guijun Qin; et al. (Journal of Diabetes Research)
Background. Physical activity is effective in preventing chronic diseases. However, the impact of different durations of exercise on human health is unknown, especially among people with diabetes or prediabetes. Objective. To explore the relationship between high MET hours per week and the change in glomerular filtration rate (eGFR) in the total population and different subgroups. Methods. A total of 43767 individuals from eight provinces, in China, were recruited. Logistic analysis was used to investigate the association. Participants were divided into 3 groups based on MET hours per week. The primary outcome was an eGFR≤90 mL/min/1.73 m2. Results. The average eGFR was 100.10 (92.43-106.43) mL/min/1.732. Logistic regression analysis revealed that more than 7.5 MET hours per week (equivalent to more than 150 minutes of moderate-intensity of exercise) was associated with the higher risk of the decreased eGFR even after adjusting for confounding factors (7.5 to <21: OR=1.18, 95% CI [1.09, 1.29]; ≥21: OR=1.12, 95% CI [1.05, 1.19], p for trend: 0.0047). After adjusting for confounding factors, in stratified analyses, there still existed a significant relationship among participants aged from 55 to less than 65 years, but not among participants younger than 55 or older than 65 years. Similarly, there existed a positive association between high MET hours per week and the decreased eGFR in participants without diabetes and prediabetes, but not in participants with diabetes or prediabetes, and the interactions of age and diabetic states were found. However, there was no significant difference in women or men. Conclusions. More than 7.5 MET hours per week (equivalent to more than 150 minutes per week or 60 minutes per day of moderate-intensity exercise) was associated with decreased eGFR among participants aged from 55 to less than 65 years and participants without diabetes and prediabetes, but not among participants aged younger than 55 years and older than 65 years and participants with diabetes or prediabetes. The importance of planning individualized physical activities is highlighted.